Sustainable use of Sugarcane Bagasse Ash (SBA) in interlocking concrete pavements - Criado, Tayla Castilho; Vicentini, Alan Henrique [UNESP]; Pagoto, Letícia Martelo [UNESP]; Junior, Gean Pereira da Silva [UNESP]; Akasaki, Jorge Luis [UNESP] (FapUNIFESP (SciELO), 2024)
The use of agro-industrial waste in civil construction has increased in recent decades, mainly sugarcane bagasse ash (SBA) in concrete production, partially replacing the binder or fine aggregate. This study assessed the feasibility of using unground SBA as a partial substitute for fine aggregate in concrete designed for interlocking paving blocks. The research investigated replacing 5%, 10%, 15%, and 20% of sand with SBA. The blocks were cast in hexagonal molds and subjected to compressive strength and water absorption tests. The results were compared with concrete produced without SBA (reference). The results indicated that mixtures with higher CBC incorporation rates (15% and 20%) met the required levels of strength and absorption, demonstrating the feasibility of using CBC as a partial replacement for sand in interlocking pavements. The mixture with 20% CBC showed the best strength results compared to the other replacement mixtures, with its compressive strength being the closest to the reference mixture. From the perspective of compressive strength, this proportion was the most suitable among the substitutions carried out for this application, offering a sustainable and efficient solution for reusing agro-industrial waste in civil construction.
Uso sustentável da Cinza de Bagaço de Cana-de-açúcar (CBC) em pavimentos inter-travados de concreto
Keywords: Agribusiness; Alternative materials; Industrial recycling; Paving; Sustainability